The inflammasome adaptor protein ASC promotes amyloid deposition in cryopyrin-associated periodic syndromes - Cristina Alarcón-Vila; Laura Hurtado-Navarro; Sandra V Mateo; Alejandro Peñín-Franch; Carlos M Martínez; Cristina Molina-López; María C Baños; Ana I Gómez; Javier Gómez-Román; Alberto Baroja-Mazo; Juan I Arostegui; Natalia Palmou-Fontana; et al. (EMBO Molecular Medicine)
In this Correspondence, P. Pelegrin and colleagues found that the deposition of amyloid in tissues in Cryopyrin-Associated Periodic Syndrome were promoted by the extracellular presence of the inflammasome adaptor protein ASC, opening exciting new directions in clinical practice to obtain a novel therapy towards secondary amyloidosis in inflammasomopathies.